The amazing Spider-Girl - DeFalco, Tom 1950-; Frenz, Ron 1960-; Buscema, Sal 1936- (Marvel Publishing, 2007)
Follows the adventures of May "Mayday" Parker, who learns that she cannot escape her great responsibilities and, as Spider-Girl, battles numerous enemies, including the Hobgoblin and the Black Tarantula
Keywords: Superheldin; Mädchen; Comic